Mortality and cancer after 12 versus 30 months dual antiplatelet therapy - Serebruany, Victor L.; Kim, Moo Hyun; Cabrera-Fuentes, Hector A.; Lee, Kwangmin; Cho, Young Rak; Park, Kyungil; Park, Tae Ho; Kim, Young Dae; Yoon, Sung-Cheol (Thrombosis and Haemostasis, 2017)
The optimal duration and cancer risks of antiplatelet therapy following percutaneous coronary intervention (PCI) are unclear. We compared cancer and all-cause mortality after dual antiplatelet therapy (DAPT) for the combination of clopidogrel and aspirin (ASA) versus ASA alone over 18 months follow-up in event-free patients at 12 months DAPT from the Health Insurance Review and Assessment (HIRA) dataset via the Korean Outcomes Registry Evaluating Antithrombotics (KOREA). We selected PCI patients who were event free for 12 months and maintained a consistent antiplatelet regimen for 18 more months. The primary endpoints were any cancer and all-cause mortality at 30 months follow-up after PCI. From 320,351 screened post-PCI patient HIRA records, we excluded 294,413 and qualified 25,938, constituting DAPT (n=10,992) and ASA (n=14,946) groups. The Propensity Score Matching (PSM), and Inverse Probability of Treatment Weighting (IPTW) revealed no significant differences in background demographics and clinical characteristics for DAPT versus ASA patients. At 30-months post-PCI, after massive (>91 %) exclusions, cancer risk was higher for continuous DAPT [455 (4.15 %) vs 606 (4.04 %); HR=1.221; 95 %CI: 1.061–1.405; p=0.005], which remained significant by PSM (p=0.006) or IPTW (p=0.007), while all-cause mortality was similar [136 (1.24 %) vs 192 (1.28 %) HR=0.999; 95 %CI: 0.736–1.135; p=0.993]. This analysis suggests a potential mild excess cancer risk, but no mortality benefit in Korean post-PCI patients treated with DAPT for an additional 18 months beyond conventional 12 months DAPT. These data are not supporting continuing DAPT for more than one year in East Asians. Analysing cancer types and assessing potential cancer association with bleeding are warranted.
Keywords: Clopidogrel; aspirin; cancer; mortality; registry; Korean